Estudo exploratório-interventivo no tratamento da obesidade segundo o protocolo Beck "Pense magro" - Barbosa, Andréia de Lima (2017)
Obesity is a current disease of great prevalence in Brazil and in the world. It is a multifactorial condition that involves emotional, cognitive and behavioral aspects. Cognitive Behavioral Therapy (CBT) has been used with proven efficacy in the treatment of obesity and its comorbidities, such as anxiety and depression indexes. This paper aims: to present the adaptation of the Beck Think Thin Protocol to a psychotherapeutic group of obese post-bariatric patients, with weight regain, in parallel psychiatric treatment at the Ambulatory of Eating Disorders of HC / UFU, from where they were referred and to evaluate the impact of this intervention on the anxiety, depression and weight (BMI) indices of the participants. Three participants were selected according to the inclusion / exclusion criteria of the study, however one did not complete all the stages of the study. The study was carried out in three stages: 1) three individual sessions to interviews, initial anthropometric measurements and Beck Anxiety Inventory (BAI) and Beck Depression Inventory (BDI); 2) eight sessions were performed in a group of psychotherapeutic intervention according to the Think Thin protocol and, at the end, new anthropometric measurements and inventories replication; and 3) follow-up three months after the end of the group, retesting the measures collected in the previous two stages, to evaluate the maintenance of the results achieved with the intervention performed. The results showed an impact of the intervention on depressive symptoms and weight of the participants, but these results, for the most part, were not maintained in the last stage; The anxiety levels of the participants had their indexes high throughout the research, despite the satisfaction analysis of the participants about the service offered have had positive results. We discuss the hypotheses that variables such as number of sessions and chronicity of the participants' emotional disorders may be related to these results.